Synthesis and fluorescence properties of side-chain carboxylated 5,9-diaminobenzo[a]phenoxazinium salts - Frade, Vânia H. J. (2005)
The efficient synthesis of a series of novel side-chain carboxylated 5,9-diaminobenzo[a]phenoxazinium salts is described. The ring system was prepared by the reaction of 5-alkylamino-2-nitrosophenol hydrochlorides with the appropriate N-alkylated-naphthylamine. Evaluation of the visible and fluorescence properties of the cationic dyes was carried out in ethanol and water at physiological pH. In both solvents they showed intense visible absorption maxima in the range 500-638 nm (ethanol) and 625-650 (water), and fluoresced strongly, with fluorescence maxima from 612 to 669 nm (ethanol) and from 654 to 685 nm (water). A wide variation in fluorescence quantum yields is observed, ranging from 0.051 to 0.50 and 0.065 to 0.32 in ethanol and water, respectively.